Management of thrombocytopenia in cancer. Issue 164 (April 2018) - Castaman, Giancarlo; Pieri, Lisa
Abstract: Thrombocytopenia is a common finding in cancer patients and can have different and/or multifactorial pathogenesis. While in solid tumors it occurs often as a consequence of chemotherapy treatment, it is frequently observed at diagnosis in patients with hematological malignancies being aggravated to a potentially life-threatening level during chemotherapy. Other associated conditions (infections, drugs, consumption coagulopathy etc.) can add to influence the degree of thrombocytopenia and the inherent risk of bleeding and they should be recognized and corrected to improve platelet count. Platelet transfusion remains the cornerstone of treatment, but its use should always be weighted taking into consideration the actual risk of bleeding to avoid inappropriate use and wasting of resources. While in hematological malignancies a threshold level of 10, 000 platelets/μL is widely accepted as the minimal level prompting prophylactic platelet transfusion, this limit is less frequently observed in patients with solid tumors and platelet transfusions are usually administered for a few days, possibly at a higher platelet level. Alternative treatments for the latter patients including thrombopoietin-mimetic agents are increasingly used and found to be promising.